Dennis Patterson on Wittgenstein - V. V. Ogleznev (Омский научный вестник: Серия "Общество. История. Современность")
Dennis Patterson, modern American legal theorist, is one of the active supporters of the importance and significance of later Wittgenstein’s ideas for resolving legal philosophy problems, including legal indeterminacy problem. On the basis of Wittgenstein’s ideas about rule-following and acting in accordance with rule, he developed his own special approach to law and legal interpretation. Although there are some doubts and possible objections that he understood and interpreted «Philosophical Investigations» correctly, it should be recognized that Patterson made a full-scale (and sometimes very convincing) attempt to explicate Wittgenstein’s thoughts in a quite different context, namely, in the context of legal theory. His treatment of wittgensteinian philosophy of language continues to be interesting and sound, despite the criticisms that have been made against his approach. It is in fact very hard to find among modern legal philosophers or theorists someone who could interpret Wittgenstein in a more sophisticated way than Patterson has done